The Relationship Between Collagen Proportionate Area and Hepatitis B Surface Antigen Levels in E Antigen Positive Hepatitis B Cirrhosis - Shi, Qiangwei; Yu, Rui; Sun, Qian; Wang, Chunfeng; Yao, Jianning; Zhang, Lianfeng (Turkish Journal of Gastroenterology, 2022)
Background: Quantitative serum hepatitis B surface antigen (HbsAg) has been widely used as a biomarker for treatment response and prognosis in chronic hepatitis B infection, and has recently been found associated with liver histology in e-antigen positive patients. A histological measurement as a continuous variable—collagen proportionate area (CPA)—is appropriate to assess liver fibrosis degree and substages cirrhosis. We, therefore, aimed to explore the association between serum quantitative HBsAg and CPA in e antigenpositive hepatitis B cirrhosis. Methods: Liver fibrosis staging was evaluated by METAVIR semiquantitative scoring system, only patients with METAVIR fibrosis stage 4 were included. All liver sections were stained with picroSirius red for determination of collagen quantification by digital image analysis. Results: Mean CPA value was 23.46%. The percentage of patients with different classification of CPA (<20%, 20-30%, >30%) were 25.8%, 57.8%, and 16.4%, respectively. A modest correlation was found between CPA and serum HBsAg level (r = –0.306, P =.001). Hepatitis B surface antigen level is independently associated with CPA in multivariable linear regression analyses. Conclusion: Serum HBsAg levels can predict liver fibrosis determined by CPA in HBeAg-positive hepatitis B cirrhosis.